2007
DOI: 10.1007/s11524-007-9188-0
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Abuse among Gay and Bisexual Men: Risk Correlates and Health Outcomes

Abstract: Little is known about the patterns and types of intimate partner abuse in same-sex male couples, and few studies have examined the psychosocial characteristics and health problems of gay and bisexual men who experience such abuse. Using a cross-sectional survey sample of 817 men who have sex with men (MSM) in the Chicago area, this study tested the effect of psychological and demographic factors generally associated with intimate partner abuse and examined their relationship to various health problems. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
168
6
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(225 citation statements)
references
References 23 publications
(26 reference statements)
24
168
6
7
Order By: Relevance
“…In relation to victimization, 28.6% of the participants reported the occurrence of minor physical abuse without sequelae, 11.9% reported severe physical abuse without sequelae, 10.7% reported minor physical abuse with sequelae and 1.2% reported severe physical abuse with sequelae. Although the studies developed in this area generally do not seek to distinguish between physical abuse with sequelae and physical abuse without sequelae, it is possible to see similarities in their prevalence rates, which range between 7.9% and 31% (Antunes & Machado 2005;Costa et al, 2009;Edwards & Sylaska, 2013;Finneran & Stephenson, 2013;Halper et al, 2004;Houston & McKirnan, 2007;Matte & Lafontaine, 2011;Pantalone et al, 2012;Ramachandran et al, 2010;Turell, 2000;Yu et al, 2013), as well as differences, as the rates found in this study are lower than the results of other studies that report rates between 45.1% and 89.9% (Blosnich & Bossarte, 2009;Craft & Serovich, 2005;Greenwood et al, 2002). Again, the social stigma of domestic violence may contribute to explaining the lower volume of reports of this type of abuse by participants (Paiva & Figueiredo, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to victimization, 28.6% of the participants reported the occurrence of minor physical abuse without sequelae, 11.9% reported severe physical abuse without sequelae, 10.7% reported minor physical abuse with sequelae and 1.2% reported severe physical abuse with sequelae. Although the studies developed in this area generally do not seek to distinguish between physical abuse with sequelae and physical abuse without sequelae, it is possible to see similarities in their prevalence rates, which range between 7.9% and 31% (Antunes & Machado 2005;Costa et al, 2009;Edwards & Sylaska, 2013;Finneran & Stephenson, 2013;Halper et al, 2004;Houston & McKirnan, 2007;Matte & Lafontaine, 2011;Pantalone et al, 2012;Ramachandran et al, 2010;Turell, 2000;Yu et al, 2013), as well as differences, as the rates found in this study are lower than the results of other studies that report rates between 45.1% and 89.9% (Blosnich & Bossarte, 2009;Craft & Serovich, 2005;Greenwood et al, 2002). Again, the social stigma of domestic violence may contribute to explaining the lower volume of reports of this type of abuse by participants (Paiva & Figueiredo, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is imperative to note that the vast distribution of prevalence rates documented in different studies of intimate abuse among same-sex partners has been commonly associated with methodological problems (Donovan et al, 2006;. Murray, Mobley, Buford, & Seaman-DeJohn, 2006/2007. In particular, these methodological problems are related to the characteristics of the studies' samples (Buller, Devries, Howard, & Bacchus, 2014;Burke & Follingstad, 1999;Rohrbaugh, 2006;Tjaden & Thoennes, 2000) and the nature of the measure, the type of instruments, and the defi nition of intimate abuse (Buller et al, 2014) used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies report on HIV seroconversion resulting from IPV victimization, 67 review the scant data pertinent to HIV and IPV victimization in gay men, 68 and demonstrate an association between IPV victimization and increased physical and mental health problems in gay and bisexual men. 69 …”
Section: Health Effects Associated With Ipv Victimization Of Menmentioning
confidence: 99%
“…[31] Similar to patterns of victimization of heterosexual IPV, gay men in abusive relationships have higher rates of depression and other mental health issues, participate in high-risk sexual behavior, and utilize illegal substances than those who are not in an abusive relationships. [32] Among Hispanic MSM, depression has been reported in approximately 25%-33%. [24] The Multicenter AIDS Cohort Study (MACS) study reported high rates of depressive symptoms among gay/bisexual men.…”
Section: Factors Associated With Mssipvmentioning
confidence: 99%